The infamous Dakota War Trials of 1862 revenge, military law and the judgment of history - Haymond, John A. 1967- (McFarland & Company, Inc., Publishers, 2016)
"This book examines the Dakota War trials from the perspective of 19th century military law. The author discusses the causes and far-reaching consequences of the war, claims of widespread atrocities, the modern debate over the role of culture in lawful warfare and how the war has been depicted by historians"...